Big-Five studies in Croatia: Big-Five relations with other personality instruments - Knezović, Zvonimir; Mlačić, Boris; Bubaš, Goran (1998)
The aim of this study was to identify the relations between the Big-Five (represented by Goldberg's 50 bipolar rating scales) and two other personality instruments, namely, Eysenck's EPQ and MMPI-201 (Croatian short version of the original instrument) and a Croatian verbal test of intellignece (M-Series) in the Croatian population. The relations between 50-BRS and EPQ were as expected - Extraversion scale (EPQ) correlated most highly with Extraversion scale (50-BRS) ; Psychoticism scale (EPQ) correlated most highly with two 50-BRS scales - Agreeableness and Conscietiousness ; and Neuroticism scale (EPQ) with 50-BRS Emotional Stability scale. Additional results were that Intellect scale (50-BRS) had the highest correlation with EPQ Extraversion scale and another significant correlation with EPQ Psychoticism scale. The relations between 50-BRS and the MMPI indicate that the MMPI is very well represented by two domains in terms of the Big-Five: Emotional Instability and Introversion, with a relative lack of reperesentation of other domains from the Big-Five. The relations between 50-BRS and M-Series were as following: subtest Analogies (M-Series) had significant correlations with three 50-BRS scales: Intellect, Emotional Stability and Conscientiousness, subtest Similarities and Differences (M-Series) had significant correlations with two 50-BRS scales: Agreeableness and Conscietiousness ; subtest Complex problems had significant correlation with the Agreeableness scale
Projekt MZOS
ENG